2020
DOI: 10.1155/2020/6136105
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Protective Effects and the Underlying Mechanism of Dexmedetomidine

Abstract: Dexmedetomidine (DEX) is a highly selective α2 adrenergic receptor (α2AR) agonist currently used in clinical settings. Because DEX has dose-dependent advantages of sedation, analgesia, antianxiety, inhibition of sympathetic nervous system activity, cardiovascular stabilization, and significant reduction of postoperative delirium and agitation, but does not produce respiratory depression and agitation, it is widely used in clinical anesthesia and ICU departments. In recent years, much clinical study and basic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 105 publications
(123 reference statements)
4
103
0
Order By: Relevance
“…DEX has pulmonary protective benefits in lung injury cases through its effect on pulmonary vascular ischemia-reperfusion injury and inflammatory cytokine release. 11 Further, DEX improves arterial oxygenation during OLV and decreases the recovery phase duration and postoperative complications in adult patients undergoing thoracic surgery. [12][13][14] However, the underlying molecular mechanism of DEXrelated protective effects on post-VATS lung injury remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…DEX has pulmonary protective benefits in lung injury cases through its effect on pulmonary vascular ischemia-reperfusion injury and inflammatory cytokine release. 11 Further, DEX improves arterial oxygenation during OLV and decreases the recovery phase duration and postoperative complications in adult patients undergoing thoracic surgery. [12][13][14] However, the underlying molecular mechanism of DEXrelated protective effects on post-VATS lung injury remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the logistic regression model including analysis of baseline neurological status, type of surgery as well as intraoperative pro les revealed potential protective effects of dexmedetomidine. Dexmedetomidine has been reported to mitigate neuroin ammatory cascades, and inhibit catecholamine and glutamate release, thereby preventing regional cerebral ischemia [2,11], which commonly occurs during cranial surgery [1,10]. In addition, plausible mechanisms of neuroprotective effects of dexmedetomidine include the attenuation of neuronal necrosis, apoptosis, autophagy through the effects of an increase of focal adhesion kinase phosphorylation in hippocampus, inducing increases of brain derived neurotrophic factor expression [25] as well as inhibiting lipopolysaccharide-induced astrocyte pyroptosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…Because the half-life of serum HMGB1 was only 17 min [33], despite the postoperative serum HMGB1 level remained unchanged in the control group, an increase in intraoperative serum HMGB1 level may likely present otherwise the postoperative resolution should be observed. Dexmedetomidine inhibits the HMGB1/TLR4 pathway [2,34], and its' cytoprotective effects may mitigate release of in ammatory mediators from injured cell [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, DEX activates α 2 adrenergic receptors and acts as a sedative agent by blocking signal transduction in the nucleus coeruleus near the fourth ventricle [ 7 ]. In recent years, clinical and basic research has confirmed that DEX has a protective effect against lung injury [ 8 ]. One study has shown that DEX can reduce lung inflammation in septic rats by inhibiting the TLR4/NF- κ B pathway [ 9 ].…”
Section: Introductionmentioning
confidence: 99%